The world will be edging toward a Global Recession (The Outlook of Education) - Thobias Sarbunan (Proceeding International Conference on Religion, Science and Education, 2023)
This study focused on the outlook of education between the new era and the global recession, so a literature study was adopted to utilize this topic. According to a new study by the World Bank, the world may be edging toward a global recession in 2023. The study finds that central banks should continue efforts to control inflation. However, according to the study, it will require concerted action by various policymakers. Global coordination can go a long way toward increasing food and energy supplies. For energy commodities, policymakers should accelerate the transition to low-carbon energy sources and introduce measures to reduce energy consumption. To strengthen global trade networks. Policymakers should cooperate to alleviate global supply bottlenecks. They should support a rules-based international economic order that guards against the threat of protectionism and fragmentation that could further disrupt trade networks.